Intégration de corpus de petite taille et d'outils multilingues dans un dispositif de formation hybride centré sur les tâches - Krastanka Bozhinova (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This study explores how didactic activities for the development of French learners' written production can be organized in an exolingual situation. It presents the results of an action research, conducted in a Bulgarian university context with international learners of French L3, who were also advanced speakers of English L2 using it as their medium of instruction. The applied social and training tasks integrate the use of digital resources in a blended learning system to improve the participants' ability to write texts corresponding to the discourse and pragmatic norms. The analysis focuses on the effect of mediation, reflexive processing of small corpora, and work with multilingual digital tools that build learners' autonomous skills.